Phylogeny more than plant height and leaf area explains variance in seed mass - Wang, Yingnan; Wang, Yang; Yu, Fei; Yi, Xianfeng (Frontiers in Plant Science, 2023)
Although variation in seed mass can be attributed to other plant functional traits such as plant height, leaf size, genome size, growth form, leaf N and phylogeny, until now, there has been little information on the relative contributions of these factors to variation in seed mass. We compiled data consisting of 1071 vascular plant species from the literature to quantify the relationships between seed mass, explanatory variables and phylogeny. Strong phylogenetic signals of these explanatory variables reflected inherited ancestral traits of the plant species. Without controlling phylogeny, growth form and leaf N are associated with seed mass. However, this association disappeared when accounting for phylogeny. Plant height, leaf area, and genome size showed consistent positive relationship with seed mass irrespective of phylogeny.Using partial R 2 s, phylogeny explained 50.89% of the variance in seed mass, much more than plant height, leaf area, genome size, leaf N, and growth form explaining only 7.39%, 0.58%, 1.85%, 0.06% and 0.09%, respectively. Therefore, future ecological work investigating the evolution of seed size should be cautious given that phylogeny is the best overall predictor for seed mass. Our study provides a novel avenue for clarifying variation in functional traits across plant species, improving our better understanding of global patterns in plant traits.